2020
DOI: 10.3390/metabo10100390
|View full text |Cite
|
Sign up to set email alerts
|

Breathomics in Asthmatic Children Treated with Inhaled Corticosteroids

Abstract: Background: “breathomics” enables indirect analysis of metabolic patterns underlying a respiratory disease. In this study, we analyze exhaled breath condensate (EBC) in asthmatic children before (T0) and after (T1) a three-week course of inhaled beclomethasone dipropionate (BDP). Methods: we recruited steroid-naive asthmatic children for whom inhaled steroids were indicated and healthy children, evaluating asthma control, spirometry and EBC (in asthmatics at T0 and T1). A liquid-chromatography–mass-spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…The detection of phosphatidylglycerol, N-acryloylglycine and tiglylglycine in earlyonset asthma [21] are associated with fatty acid metabolism, which is consistent with data suggesting lipid dysregulation in asthma [120,123]. Glycerophospholipid metabolism has been shown to be altered in BALF from animal models of allergic asthma [136] and in asthmatic subjects indicating the possible role of glycerophospholipid in the pathogenesis of asthma and of airway epithelial injury [50,137].…”
Section: Lipid Metabolism and Inflammationsupporting
confidence: 83%
See 1 more Smart Citation
“…The detection of phosphatidylglycerol, N-acryloylglycine and tiglylglycine in earlyonset asthma [21] are associated with fatty acid metabolism, which is consistent with data suggesting lipid dysregulation in asthma [120,123]. Glycerophospholipid metabolism has been shown to be altered in BALF from animal models of allergic asthma [136] and in asthmatic subjects indicating the possible role of glycerophospholipid in the pathogenesis of asthma and of airway epithelial injury [50,137].…”
Section: Lipid Metabolism and Inflammationsupporting
confidence: 83%
“…When comparing the non-severe asthma group to severe asthma, Carraro et al measured metabolites in EBC related to inflammation, 20-hydroxy-PGF2a, thromboxane B2, and 6-keto-prostaglandin F1a [ 30 ]. The occurrence of inflammatory mediators in EBC is a common phenomenon in pediatric [ 120 ] and adult asthma [ 121 , 122 ]. A high omega-6 to omega-3 fatty acid ratio has been suggested to be pro-inflammatory and pro-allergic.…”
Section: Discussionmentioning
confidence: 99%
“…New techniques include the use of -omics technology, such as transcriptomics, proteomics and metabolomics, to create a detailed profile of the asthma features. One of the latest applications is the metabolic profiling of the breath of asthma patients before and after ICS treatment ( Ferraro et al, 2020 ). Moreover, the aim of the ongoing SMART clinical trial (NCT04194814), started in 2019, is to test new non-invasive methods to evaluate biomarkers for skin structure and function variations.…”
Section: Discussionmentioning
confidence: 99%
“…Another clinical trial showed that the relative abundance of four metabolites, i.e., lactate, formate, butyrate, and isobutyrate, were significantly higher in EBCs of children with asthma than in healthy controls [ 22 ]. Three metabolites (prostaglandins, fatty acids, and glycerol phospholipids) can be used as biomarkers of breathomics to distinguish asthma children from healthy children [ 23 ]. Obesity and asthma are closely linked, and, interestingly, the EBC metabolomics of obese asthmatics is characterized by a unique metabolic spectrum compared to obesity or asthma alone [ 84 ].…”
Section: Integrative Analysis Of Asthma-related Metabolites and Metabolic Pathways In Different Samplesmentioning
confidence: 99%